Facile synthesis of Fe2O3, Fe2O3@CuO and WO3 nanoparticles: characterization, structure determination and evaluation of their biological activity - Asmaa T. Mohamed; Reda Abdel Hameed; Shahira H. EL-Moslamy; Mohamed Fareid; Mohamad Othman; Samah A. Loutfy; Elbadawy A. Kamoun; Mohamed Elnouby (Scientific Reports, 2024)
Abstract Due to their high specific surface area and its characteristic’s functionalized nanomaterials have great potential in medical applications specialty, as an anticancer. Herein, functional nanoparticles (NPs) based on iron oxide Fe2O3, iron oxide modified with copper oxide Fe2O3@CuO, and tungsten oxide WO3 were facile synthesized for biomedical applications. The obtained nanomaterials have nanocrystal sizes of 35.5 nm for Fe2O3, 7 nm for Fe2O3@CuO, and 25.5 nm for WO3. In addition to octahedral and square nanoplates for Fe2O3, and WO3; respectively. Results revealed that Fe2O3, Fe2O3@CuO, and WO3 NPs showed remarked anticancer effects versus a safe effect on normal cells through cytotoxicity test using MTT-assay. Notably, synthesized NPs e.g. our result demonstrated that Fe2O3@CuO exhibited the lowest IC50 value on the MCF-7 cancer cell line at about 8.876 µg/ml, compared to Fe2O3 was 12.87 µg/ml and WO3 was 9.211 µg/ml which indicate that the modification NPs Fe2O3@CuO gave the highest antiproliferative effect against breast cancer. However, these NPs showed a safe mode toward the Vero normal cell line, where IC50 were monitored as 40.24 µg/ml for Fe2O3, 21.13 µg/ml for Fe2O3@CuO, and 25.41 µg/ml for WO3 NPs. For further evidence. The antiviral activity using virucidal and viral adsorption mechanisms gave practiced effect by viral adsorption mechanism and prevented the virus from replicating inside the cells. Fe2O3@CuO and WO3 NPs showed a complete reduction in the viral load synergistic effect of combinations between the tested two materials copper oxide instead of iron oxide alone. Interestingly, the antimicrobial efficiency of Fe2O3@CuO NPs, Fe2O3NPs, and WO3NPs was evaluated using E. coli, S. aureus, and C. albicans pathogens. The widest microbial inhibition zone (ca. 38.45 mm) was observed with 250 mg/ml of WO3 NPs against E. coli, whereas using 40 mg/ml of Fe2O3@CuO NPS could form microbial inhibition zone ca. 32.86 mm against S. aureus. Nevertheless, C. albicans was relatively resistant to all examined NPs. The superior biomedical activities of these nanostructures might be due to their unique features and accepted evaluations.